Development of the Quizizz Application-Based Evaluation Tool for Learning Arabic for MTs│Pengembangan Alat Evaluasi Berbasis Aplikasi Quizizz pada Pembelajaran Bahasa Arab untuk MTs - Annisa Elita Rahmawati; Zulhannan; Umi Hijriyyah; Erlina; Koderi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The Quizizz application-based evaluation tool is very important to be developed to meet the needs of students when evaluating learning. This study aims to determine the validity, practicality, and effectiveness of the quizizz application-based evaluation tool for learning Arabic at MTs 1 Purbolinggo, East Lampung. This research uses the type of development or Research and Development with the ADDIE model which consists of 5 stages, namely Analyze, Design, Development, Implementation, Evaluation. The data in this study were obtained through questionnaires, interviews, observation and documentation. Questionnaires were given to students of class VIII MTs 1 Purbolinggo, interviews were conducted with teachers and several students, observations were made in class during product trials, then documentation was obtained from student learning outcomes. Then to test the feasibility of the product the researcher received assistance from the validators in this study, namely material experts, media experts, and Arabic subject teachers. The data collection method in this study was through small group tests and large group tests. The final results of the research on the development of an evaluation tool based on the quizizz application are based on a validity test, namely validation from material experts gets results of 3.67 with very valid criteria, validation of media experts gets 3.55 which means very valid, validation of education practitioners experts gets results of 3.75 which means very valid. In the assessment of students in the small group trial, the final result was 3.28 with very interesting criteria, the large group trial obtained a result of 3.41 with very interesting criteria. It can be concluded that the quizizz application-based evaluation tool developed for learning Arabic is very suitable as a learning evaluation tool at MTs Muhammadiyah 1 Purbolinggo, East Lampung.